Comparison study between tween 20 and tween 80 as an edge activator for preparation of transdermal ondansteron HCL transfersomal nano particles - Hind AbdAlameer Hadi; Ahmed Hashim Hussein (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
In ordinary clinical practice, poor patient compliance with oral and parenteral drug administration modalities is a prevalent problem. As a result, pharmaceutical research has developed a strong interest in the transdermal route of drug delivery. They are noninvasive, self-administered administration techniques that can improve patient compliance. However, the barrier function of the skin’s top layer presents the biggest challenge for transdermal delivery systems. Ionized chemicals and compounds with molecular weights greater than 500 Da cannot pass through skin. As a result, this method can only be used to deliver a few medicines. A possible solution to this issue is to include the medications in transfersomes. Transfersomes are vesicles composed of phospholipids and edge activators, used to transport drug from outer skin layer into the systematic circulation through a semipermeable membrane. Tween 20, 80 (Polysorbates) are edge activators employed in medicines for a variety of reasons, including modifying the absorption of active ingredients. Ondansetron is an antiemetic medication that has been given parenterally and orally. Formulating this medication as transdermal transfersomes may provoke a great advantage in medical adherence